A study on the deployment of expenditure in Alor Gajah Municipal Council / Nur Syuhada Azizan and Siti Jamilah Azahar - Azizan, Nur Syuhada; Azahar, Siti Jamilah (Faculty of Administrative Science and Policy Studies, 2013)
In general, local government is part of the three tier government structure which is Federal government, State government and Local government. Local government in Malaysia is essentially an urban phenomenon, which comes to say that the existence and functions of local government should be seen as an essential system of administration to govern modern areas for the society. Besides, local government has the responsibility for numerous services related to housing, water supply, waste management, taxation, land assessment and other matters (Chin Abdullah, 2008). Therefore, local government has to allocate their expenditure for each service that provided to the public effectively and efficiently. It is important for the local government to have capability to manage their expenditure in order to strengthen economic growth through effective distribution of resources.